Drug-induced gingival overgrowth: A critical insight into case reports from over two decades - Pramod Samudrala; Vijay Kumar Chava; Tanguturi Sri Chandana; Rachakonda Suresh (Wolters Kluwer Medknow Publications, 2016)
Drug-induced gingival overgrowth (DIGO) is a well-recognized adverse effect of certain systemic medications. Calcium channel blockers, anticonvulsants, and immunosuppressants are frequently implicated drugs in the etiology of DIGO. Drug variables, plaque-induced inflammation, and genetic factors are the three important factors in the expression of gingival changes after systemic medication use. Careful clinical examination and thorough history taking form the basis for diagnosis of DIGO. Histopathological examination is often neglected; however, it is an important aid that helps in differential diagnosis. Cessation or change of drug and meticulous plaque control often leads to regression of the lesion, which however might need surgical correction for optimal maintenance of gingival health. The purpose of the present article is to review case reports and case series published in the last two decades and to assimilate and compile the information for clinical applications such as diagnosis and therapeutic management of DIGO.